Perioperative Diagnosis, Risk Stratification and Organ-Protective Management of Cardiac Surgery–Associated Acute Kidney Injury in Infants and Young Children with Congenital Heart Disease: A Narrative Review - Ismailov Saydimurad Ibragimovich; Khaydarov Alisher Erkinovich; Khalikulov Khusan Gazixanovich; Irmatov Sarvar Hikmatillaevich; Mardonov Jamshid Normurotovich (American Journal of Bioscience and Clinical Integrity, 2026)
Acute kidney injury (AKI) remains one of the most frequent and clinically significant complications following congenital heart surgery in infants and young children. Cardiac surgery–associated acute kidney injury (CSA-AKI) is associated with prolonged mechanical ventilation, extended intensive care unit stay, increased need for vasoactive support and renal replacement therapy, and worse short-term clinical outcomes. The burden of CSA-AKI is particularly high in neonates and infants undergoing complex procedures or prolonged cardiopulmonary bypass. Although traditional diagnostic criteria based on serum creatinine and urine output remain clinically essential, their sensitivity for early detection is limited. This has stimulated growing interest in multimodal risk stratification strategies that integrate perioperative hemodynamic parameters, tissue perfusion markers, and renal and cardiac biomarkers. Current evidence increasingly supports a comprehensive organ-protective approach that includes optimized anesthesia, goal-directed perfusion during cardiopulmonary bypass, echocardiography-guided hemodynamic management, careful fluid stewardship, and timely initiation of peritoneal dialysis in selected high-risk patients. This narrative review summarizes current evidence on the epidemiology, perioperative risk factors, diagnostic challenges, and evolving preventive and therapeutic strategies for CSA-AKI in infants and young children with congenital heart disease.